2020
DOI: 10.1038/s41598-020-61447-8
|View full text |Cite
|
Sign up to set email alerts
|

Object responses are highly malleable, rather than invariant, with changes in object appearance

Abstract: theoretical frameworks of human vision argue that object responses remain stable, or 'invariant', despite changes in viewing conditions that can alter object appearance but not identity. Here, in a major departure from previous approaches that have relied on two-dimensional (2-D) images to study object processing, we demonstrate that changes in an object's appearance, but not its identity, can lead to striking shifts in behavioral responses to objects. We used inverse multidimensional scaling (MDS) to measure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 98 publications
(144 reference statements)
1
29
0
Order By: Relevance
“…The effect of the object real-size in parietal cortex has been investigated in the context of object affordances (using real objects) and limited to small graspable objects (Cavina-Pratesi, Goodale, & Culham, 2007;Fabbri et al, 2017;Kourtis, Vandemaele, & Vingerhoets, 2018). However, recent evidence suggests that properties we extract from objects vary depending on the viewing format: physical properties (e.g., object size, weight, elongation) are relevant when watching real 3D objects, but not 2D images (Holler, Fabbri, & Snow, 2020). Consolidating these findings, we conclude that the manipulability effect observed in IPS is unlikely to be explained by imagined object physical size.…”
Section: Tools and Graspability: Partially Overlapping Conceptsmentioning
confidence: 99%
“…The effect of the object real-size in parietal cortex has been investigated in the context of object affordances (using real objects) and limited to small graspable objects (Cavina-Pratesi, Goodale, & Culham, 2007;Fabbri et al, 2017;Kourtis, Vandemaele, & Vingerhoets, 2018). However, recent evidence suggests that properties we extract from objects vary depending on the viewing format: physical properties (e.g., object size, weight, elongation) are relevant when watching real 3D objects, but not 2D images (Holler, Fabbri, & Snow, 2020). Consolidating these findings, we conclude that the manipulability effect observed in IPS is unlikely to be explained by imagined object physical size.…”
Section: Tools and Graspability: Partially Overlapping Conceptsmentioning
confidence: 99%
“…This is the case even when considering experimental settings with different delivery apparatus. For instance, Holler & Snow (2020) found convergent results in an experimental setting where the real-world objects were handled physically whereas the pictures were manipulated on a computer screen. Our complimentary results were obtained in an experimental setting in which both real objects and pictures are physical manipulated.…”
Section: Discussionmentioning
confidence: 93%
“…1 Yet, there is very little research into the possible effects of affordances in this context and, crucially, in the similarity judgement paradigm for categorization tasks. For instance, while Holler and Snow (2020) recently found differences in how images and real-world objects are categorized, they did so without paying attention to the hypothesis that affordances may be responsible for those differences. Also, Castellini et al (2011) found that affordances potentiated object recognition but did not investigate the effect on similarity judgements.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported stronger affordance effects with real objects (Snow et al 2011, Gomez et al 2017) compared to 2D images of objects (Bub and Masson 2010, Squires et al 2016, Bub et al 2018). In a recent study, the categorisation of real objects led to the use of factors relating both conceptual and physical characteristics, whereas 2D-images were mostly categorised on the basis of conceptual characteristics alone (Holler et al 2020). Taken together, these differences might explain differences in activation patterns identified between the Grezes et al (2003) grasp categorisation study, and ours, which involved turning a real object with a reaching and wrist rotation movements.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicated functional interactions between 'dorso-dorsal' LPMd and ventral stream area LOCT in trials where hand posture and object orientation were incongruent, suggesting a direct integration between dorsal and ventral stream areas when preparing incongruent object manipulations (van Polanen and Davare 2015). Integrating ventral stream information during object manipulation dynamically with dorsal stream structures would suggest that affordance effects represent an influence of action semantics in tasks that do not require object categorisation or understanding, such as object manipulation (Creem and Proffitt 2001, Till et al 2014, van Elk et al 2014, Holler et al 2020.…”
Section: The Neural Correlates Of Affordances On Posture Representations In the Brainmentioning
confidence: 99%